Complication risks of invasive dental procedures in HIV/AIDS patients - Cahyati, Miftakhul; Rahmayanti, Febrina (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2008)
A total number of people living with HIV reached since it was first reported. Indonesia is on the brink of rapidly worsening AIDS epidemic. Oral health was a frequent problem among HIV-infected person. Opportunistic oral lesions and infections were often one of the first manifestations of HIV. The aim of this literature review was to discuss complication risks and management undergoing invasive dental procedures. Thereby, dentists have been expected to increase awareness of dental treatment needs for HIV-infected patients by pay attention to applied standard procedure. The complications of HIV-infected patients were reported minor, self-limiting, non-life threatening and readily treated. Treatment planning for the patient with HIV follows the same sequences as with other patients priorities are to assuage pain, restore function, prevent further disease and consider esthetic results. We concluded that no different complication risks between HIV-infected and non-infected. Dentists can provide care for HIV-infected patients with assessing the current immunosuppression stage, intake systemic medications, opportunistic infection potential and minimize contagion possibility to dental care professional or other patients.